Tingkat resistensi insektisida emamektin benzoat terhadap ulat krop Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) di Kabupaten Cianjur, Jawa Barat: Resistance level of emamectin benzoate insecticide to Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) in Cianjur Regency, West Java - Sinyong, Kristoforus; Mubin, Nadzirum; Prijono, Djoko (Perhimpunan Entomologi Indonesia, 2023)
The cabbage crop caterpillar, Crocidolomia pavonana, that can be very damaging to Brassicaceae plants in Indonesia, particularly in the Cianjur Regency. Farmers in the area have been using synthetic insecticides like emamectin benzoate to control this pest, but it seems that continuous use of these insecticides can lead to resistance in the pest. This research aimed to determine the level of resistance and distribution of emamectin benzoate in C. pavonana in Cianjur Regency. Field populations of C. pavonana were collected from five villages in three districts in Cianjur Regency. As a comparison, a laboratory population was used to determine the resistance ratio. All populations were tested for toxicity to determine the LC50. The results showed that populations of C. pavonana from Cianjur Regency were still susceptible to emamectin benzoate. Treatment at 22.08 í— 10-4 mg a.i/l concentration in 72 hours after treatment showed that the population's mortality was >90%. The resistance ratios of C. pavonana in Cianjur Regency were quite concerning (resistance indocation), with a range of 1.33–2.01 indicating resistance to emamectin benzoate was moderate. Interestingly, the Sindang Jaya population showed the highest resistance ratio. It's worth noting that over 90% of farmers in the region use this insecticide in the field, which supports the idea of resistance to the chemical. This study provided valuable insight into the distribution of insecticide used and resistance levels of C. pavonana in the area support each other.